Classroom Techniques Used By The Teacher To Develop Students' English Reading Skill At Mts N 1 Grobogan In 2015/2016 Academic Year: A Naturalistic Study - Mubarokah, Rizki Aulia Lailatul, Prof. Dr. Endang Fauziati, M. Hum, Nur Hidayat, M. Pd (2016)
This study is carried out to describe classroom techniques used by the teacher to develop students' English reading skill at MTs N 1 Grobogan. The aims of this research are: (1) to describe the types of classroom techniques used by the teacher to develop students' English reading skill, (2) the purpose of using each classroom technique, (3) the teacher's roles, (4) the student's roles, and (5) instructional materials used by the English teachers at MTs N 1 Grobogan. The kind of this research is descriptive qualitative research especially naturalistic study in analyzing the data. The methods of collecting data in this research are observation, interview, and documentation. This research uses data triangulation, method triangulation, and review informant to prove the validity. The finding of the study shows that there are some classroom techniques used by English teachers at MTs N 1 Grobogan such as skimming and scanning, reading aloud, silent reading, and translation. The teachers have roles as material developer, monitor, motivator, controller, model, counselor and evaluator. The students have roles as learner, subject of learning, performer, and monitor and evaluator of his or her own progress. There are some materials used by English teachers, such as English book, workbook, dictionary, and another source from internet as supplementary material. The conclusion of this research is that English teacher at MTs N 1 Grobogan used various classroom techniques to improve the students' reading ability. Various techniques can make the students interested in English teaching-learning process. Various techniques also make the students not bored when learning process. It does not make the class monotonous. The students become more active and creative. Based on the result, apparently, classroom techniques used by the teacher have important role in the teaching-learning process.